2021
DOI: 10.3390/quat4020016
|View full text |Cite
|
Sign up to set email alerts
|

Human Activities, Biostratigraphy and Past Environment Revealed by Small-Mammal Associations at the Chalcolithic Levels of El Portalón de Cueva Mayor (Atapuerca, Spain)

Abstract: The Chalcolithic levels of El Portalón de Cueva Mayor (Atapuerca, Burgos, Spain) offer a good opportunity to test whether the small-mammal contents of different archaeo-stratigraphical units may be useful to characterize them as independent entities. With that purpose, we studied representative samples of small-mammal remains from the two main contexts identified: the Early Chalcolithic (EC) funerary context and the Late Chalcolithic (LC) habitat/stabling context, with the latter comprising three different arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…A similar situation in which the percentage of small mammal synanthropic taxa decreases during a burial phase is observed in the Early Chalcolithic level (5290–4850 cal. yr BP) from El Portalón cave (Sierra de Atapuerca, Burgos, less than a kilometre from El Mirador) according to Rofes et al (2021). Despite a possible delay in the response of the microfauna in MIR4 to the arid phase of MIR5 could be considered, the intensification of the human impact in the surroundings of El Mirador cave during the Bronze Age prevents from supporting this assumption (Bañuls-Cardona et al, 2017a, 2017b; Cabanes et al, 2009; Expósito et al, 2017; Rodríguez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation in which the percentage of small mammal synanthropic taxa decreases during a burial phase is observed in the Early Chalcolithic level (5290–4850 cal. yr BP) from El Portalón cave (Sierra de Atapuerca, Burgos, less than a kilometre from El Mirador) according to Rofes et al (2021). Despite a possible delay in the response of the microfauna in MIR4 to the arid phase of MIR5 could be considered, the intensification of the human impact in the surroundings of El Mirador cave during the Bronze Age prevents from supporting this assumption (Bañuls-Cardona et al, 2017a, 2017b; Cabanes et al, 2009; Expósito et al, 2017; Rodríguez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Rofes et al [26] explored the potential of micromammals to reconstruct human activities, biostratigraphy, and palaeoenvironments at El Portalón de Cueva Mayor in Spain (Early Late Chalcolithic). The authors demonstrated the differences in the small-mammal spectrum among different areas and phases of human activity (e.g., burials, prepared floors, activity floors, and fumiers) and provided the first Holocene sub-fossil record of multiple rodent, shrew, and bat species in the Sierra de Atapuerca.…”
Section: Analysis Of Fossil and Sub-fossil Assemblagesmentioning
confidence: 99%
“…The relationship between micromammals (primarily small rodents and insectivores) and the various categories of archaeological material recovered from a given site has received little attention. Apart from the Chalcolithic site of El Portalón [12], the Upper Palaeolithic sites of Peyrazet [13,14] and Taillis des Coteaux [15] and the Middle Palaeolithic site of Les Pradelles [13], relatively few studies have focused on the correlation between micromammals and archaeological material.…”
Section: Introductionmentioning
confidence: 99%